Analysis of the Financial Performance of LQ-45 Banking Companies Before and After Rights Issues - Fahrudin; Suharti, Titing; Yudhawati, Diah (Manager : Jurnal Ilmu Manajemen, 2025)
This study aims to determine whether there are significant differences in the company's financial performance before and after the implementation of the right issue action in LQ-45 index banking companies in the 2020-2023 period. Financial performance in this study is measured using current ratio and return on equity indicators. The type of data in this study is quantitative with secondary data sources. Sample collection using purposive sampling technique with sample results consisting of 4 banking companies. The analysis method was carried out with a paired samples t-test using SPSS 27. The results of this study indicate that there is a significant difference in the current ratio before and after the implementation of the right issue. Meanwhile, return on equity does not show a significant difference in the financial performance of banking companies in the LQ-45 index in the 2020-2023 period.